2021
DOI: 10.1002/cbin.11730
|View full text |Cite
|
Sign up to set email alerts
|

Porcine oviductal extracellular vesicles facilitate early embryonic development via relief of endoplasmic reticulum stress

Abstract: The key to successful in vitro embryo production (IVEP) is to mimic the natural in vivo oviductal microenvironment. Although the chemically defined media in extensive use for the in vitro culture of mammalian embryos is based on the composition of oviductal fluid, the IVEP systems in current use must still bypass the oviduct to produce embryos in vitro. Extracellular vesicles (EVs) in the oviduct are versatile intercellular delivery vehicles for maternal–embryo communication, and a lack of them can be associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…We found that under ER stress, BC cells released high levels of oxidized PDI within EVs, thereby mitigating the ROS production and consequent cell death, ultimately promoting BC cell survival. This nding is highly innovative and aligns well with the observation that, while cells continuously shed EVs at steady state, multivesicular body formation and EV release are enhanced under conditions of ER stress or oxidative stress (44,45), supporting this process of EV-mediated oxidized PDI export as a stress relief mechanism (34).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We found that under ER stress, BC cells released high levels of oxidized PDI within EVs, thereby mitigating the ROS production and consequent cell death, ultimately promoting BC cell survival. This nding is highly innovative and aligns well with the observation that, while cells continuously shed EVs at steady state, multivesicular body formation and EV release are enhanced under conditions of ER stress or oxidative stress (44,45), supporting this process of EV-mediated oxidized PDI export as a stress relief mechanism (34).…”
Section: Discussionsupporting
confidence: 78%
“…This, coupled with the potential need for tumor cells to regulate PDI activity and attendant oxidative stress within a tolerable range conducive to proliferation and drug resistance, raises the possibility that EVs may provide a release valve to manage levels of intracellular stress. Indeed, EVmediated relief of excessive ER stress has been proposed in developmental settings (34), and may be co-opted by tumor cells, indirectly exposing non-malignant recipient cells to this stress in the process.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, UF-EVs were supplemented to the embryo culture media, which showed significantly improved blastocyst development rates compared to nontreated control. Previous studies have shown that EVs are internalized by embryos ( 26 , 57 ) being able to reduce ROS levels in embryos ( 58 ), which improves blastocyst rates. However, our finding needs further investigation to understand the differences in anti-oxidation–protective effects on embryos, which are supplemented directly to culture medium compared to antioxidants that are carried by EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Embryo-maternal communication and signaling between endometrial cells during pre-implantation period is crucial in mediating embryo and endometrial growth, which both is needed for successful pregnancy. There are plethora of evidence supporting the involvement of EVs from either side in maternal-embryo cross talks in establishment of pregnancy and development of the embryo beyond the implantation ( 14 , 24 , 26 , 27 ). However, the optimal bovine UF-EV protein composition leading to successful pregnancy is yet to be established.…”
mentioning
confidence: 99%
“…Porcine O-EVs can decrease caspase-3 gene expression, decrease blastocyst cell apoptosis, and increase blastocyst formation rate. This could be caused by lowering the expression of the sXBP1, ATF4, and GRP78 genes in order to reduce embryonic ER stress ( Fu et al, 2022 ). Furthermore, O-EVs have an energy regulation effect on embryo development.…”
Section: The Role Of Evs In Embryonic Developmentmentioning
confidence: 99%